Influence of Biopolym Granulat Effects on Reduction of Ammonia Concentration in Stables of Intensive Farm Animals Breeding - Bohuslav Čermák; Jana Hnisová; Lenka Martínková; Eva Petrášková; Miloslav Šoch; Luboš Zábranský; Miroslav Maršálek (Scientific Papers Animal Science and Biotechnologies, 2023)
The living environment distress is connected currently not only with industrial production but also agriculture is biggest producer of toxic gas – ammonia (NH3) .Emissions of that gas originate mainly in the farm animals breeding and generate within storage and handling with farmyard manure, slurry, poultry excrements and litter. Agriculture influences considerably the landscape. It has impact on basic effect on soil, water and air. In assessing experiment the preparation Biopolym Granulat rumen metabolism and N-balance was found positive effects in terms of increased ammonia nitrogen, the number of ciliates and the reduction of N-compounds in feces. It was confirmed the impact on the ammonia content in well-ventilated dairy stable. The economic evaluation depends on the exercise price of milk.